Developing Long Term Low Emissions and Climate Resilient Agricultural Development Pathways for Uganda: Policy coherence and strong cross-sector and multi-stakeholder collaboration - African Group of Negotiators Expert Support; Food and Agriculture Organization of the United Nations; Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Agriculture is a key sector for Uganda’s economy and it remains highly risky largely due to its sensitivity to climate change and related impacts. Uganda embarked on a journey of developing an economy-wide long term Low-Emission and Climate-Resilient Development Strategy as well as the Agriculture Sector Long Term Low Emissions and Climate Resilient Development Pathway (Agriculture LTS) aimed at facilitating the country’s continued transformation to a green economy by prioritising adaptation and mitigation actions that increase agricultural productivity and build climate resilience of the agricultural and food systems while reducing greenhouse gas (GHG) emissions intensities in the sector.